PRODUCTIVE TECHNOLOGIES FOR TEACHING GRAMMAR - Musurmonova Saodat Jamshidovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: The knowledge of grammatical rules enable learners to know and apply how such sentence patterns should be put together. Further, grammar is thought to furnish the basis for a set of language skills: listening, speaking, reading and writing.